Margaret Mead - Ziesk, Edra. (New York : Chelsea House, 1990)
A biography of the now legendary anthropologist famous for her studies of primitive cultures.
Includes bibliographical references (p. 104) and index.
Keywords: Mead, Margaret, -- 1901-1978 -- Juvenile literature; Mead, Margaret, -- 1901-1978.; Women anthropologists -- United States -- Biography -- Juvenile literature; Ethnology -- Melanesia -- Juvenile literature; Anthropologists; Women -- Biography; Melanesia -- Social life and customs -- Juvenile literature